From Traditional to Modern: Cultural Integration and Innovation in Sustainable Architectural Design Education - Yunxuan, Wang; Ruikai, Yuan; Ibrahim, Nik Lukman Bin Nik (Journal of Ecohumanism, 2025)
This study explores the integration of traditional architectural culture into sustainable architectural design education to address the dual challenges of global climate change and resource scarcity. The study highlights the ecological wisdom embedded in traditional architecture, such as the thermal performance of Chinese cave dwellings and the material sustainability of Japanese wooden structures. By analyzing these cultural elements, this study identifies strategies to integrate them into modern architectural education through case studies, design workshops, and hands-on learning experiences. The findings highlight the importance of combining cultural depth with modern technology to cultivate innovative, ecologically conscious designers. A multidimensional assessment framework is proposed to evaluate students' cultural understanding, technological application, and ecological responsibility in design projects. This study concludes that the integration of cultural heritage with advanced design practices can not only enhance the sustainability of buildings, but also promote a deeper connection between modern design and local cultural characteristics. Future recommendations include the adoption of advanced tools, policy support for cultural preservation, and interdisciplinary collaboration to improve sustainable design education.